Crop diversification with crossandra A remunerative option for farmers - Reddy, A. Gopala Krishna; Nirmala, G.; Dinesh, A.; Pankaj, P. K.; Reddy, B. Sanjeeva; C. N., Anshida Beevi; Rohit, Jagriti; Narsimlu, B.; Shankar, K. Ravi; Singh, V. K.; Reddy, A. R. (Indian Farming, 2025)
Crossandra, a floriculture crop, has gained popularity among farmers due to its wide adaptability and ease of cultivation. The limited area under crossandra crop cultivation allows the crop to fetch optimum prices in the market throughout the year. However, a lack of knowledge regarding cultivation practices, available varieties, and quality planting materials poses significant challenges to its successful production. To address these issues, scientists of Farmer FIRST Programme of ICAR-CRIDA proposed an integrative approach to crossandra cultivation, providing comprehensive farm advisories throughout the crop growth cycle. This included guidance on procuring quality seedlings, applying manures and fertilizers at the right time and dosage, and implementing a dripirrigation system as part of the project. As a result, the farmer significantly increased his net returns, achieving a remarkable profit of ₹3,00,700. The success has also served as an inspiration for other farmers in his village to adopt crossandra cultivation, promoting agricultural diversity and economic growth within the community.